THE INFLUENCE OF EYD MASTERY AND EFFECTIVE SENTENCES ON WRITING OFFICIAL LETTER OF EMPLOYEE UNIVERSITY OF MUHAMMADIYAH TANGERANG - Safitri, Nurulia; Goziyah, Goziyah; Marzuki, Ismail (Universitas Muhammadiyah Tangerang, 2023)
Proficiency in writing is one of the most important skills for humans. By writing, humans can convey ideas, opinions, and ideas to others through writing. However, not all humans can be said to be proficient in writing. Therefore, humans need to practice and learn a lot in making writing by paying attention to the rules of spelling Indonesian and the use of effective sentences. By paying attention to these aspects, a writing produced will be easier to understand and understand by others